Effect of curcumin on acute chronic kidney disease due to ischemia-reperfusion syndrome - Silva,Eloiza de Oliveira (2022)
ABSTRACT Objective: To evaluate the effect of curcumin on renal function, hemodynamics, and renal oxidative profile of rats with chronic kidney disease (CKD) subjected to renal ischemia-reperfusion injury (IRI). Methods: Wistar rats, 250–300 g, distributed in four groups: Sham (n = 5), CKD simulation; CKD (n = 5), 5/6 renal ablation for CKD induction; CKD + IRI (n = 5), CKD and renal pedicle clamping for 30 minutes; and CKD + IRI+curcumin (n = 5), CKD + IRI, curcumin administration 30 mg/kg/day, orally, for 10 days. Renal function (inulin clearance, urine flow, plasma creatinine), hemodynamics (blood pressure), and oxidative profile (peroxides, TBARS, and urine nitrate, non-protein soluble thiols in renal tissue) were evaluated. Results: The CKD + IRI + curcumin group showed increased inulin clearance and reduced plasma creatinine, decreased RVR and increased RBF, decreased oxidative metabolites in urine and increased thiols in renal tissue when compared with the CKD + IRI group. Conclusion: The treatment with curcumin preserved renal function and hemodynamics of animals with acute CKD, improving oxidative profile, with reduction of oxidants and preservation of antioxidant reserve.